The process of formulating and implementing strategic planning in public sector institutions - Silva, Flávia de Araújo; Gonçalves, Carlos Alberto (Revista de Administração da UFSM, 2011)
This paper aim to discuss some models for formulation and processing of the strategic planning vis-à-vis to support management of main deliberate strategies in public institutions. We researched bibliographies of theories about practices and processes of strategy formation until the development of the document to be followed as "Strategic Plan". The units of analysis are the Audit Courts of the States and Municipalities of Brazil. It was adopted combined methods of literature review, consultations to the strategic plans of some public institutions, qualitative and quantitative research through interviews and survey. Within public institutions it was identified the favorite models used for the formulation and implementation of organizational strategic plan namely: Grumbach Method, Balanced Scorecard (BSC) and Management by Policy. The research results indicate the existence of strong team’s beliefs in the effectiveness of the "strategic planning" as a regular practice in a way that provide better overall strategic alignment. It was concluded also that the institutions researched are still in a step of acquiring apprenticeship for this instrumentalization, mainly in respect to put into action the planned actions.